Pemberdayaan Ekonomi Masyarakat Melalui Sosialisasi Platform Kerja Freelance Digital di Warung Kopi Kota Medan: Pengabdian - Jam'an Amadi; Jufri Antoni; Juliani; Fajrillah; Ari Lestari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service activity aimed to introduce digital freelance work opportunities to vocational high school (SMK) students and informal sector workers in Medan City. The method used was direct socialization at four breakfast stalls (warungs) and coffee shops, involving informal interviews regarding daily occupation and income sufficiency. The results showed that many participants were unaware of legitimate online platforms to earn extra income based on their passions. The team introduced reputable platforms such as Projects.co.id, Fastwork, and Sribu.com, while educating them on avoiding scams. This activity successfully provided new insights for students to earn pocket money without quitting school and for workers to gain side income.